Outdoor Air Pollution, Preterm Birth, and Low Birth Weight: Analysis of the World Health Organization Global Survey on Maternal and Perinatal Health - Fleischer, Nancy L. (National Institute of Environmental Health Sciences, 2014)
Background: Inhaling fine particles (particulate matter with diameter ≤ 2.5 μm; PM2.5) can induce oxidative stress and inflammation, and may contribute to onset of preterm labor and other adverse perinatal outcomes.